2010
DOI: 10.1186/1750-1326-5-26
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR kinase inhibitor Everolimus decreases S6 kinase phosphorylation but fails to reduce mutant huntingtin levels in brain and is not neuroprotective in the R6/2 mouse model of Huntington's disease

Abstract: BackgroundHuntington's disease (HD) is a progressive neurodegenerative disorder caused by a CAG repeat expansion within the huntingtin gene. Mutant huntingtin protein misfolds and accumulates within neurons where it mediates its toxic effects. Promoting mutant huntingtin clearance by activating macroautophagy is one approach for treating Huntington's disease (HD). In this study, we evaluated the mTOR kinase inhibitor and macroautophagy promoting drug everolimus in the R6/2 mouse model of HD.ResultsEverolimus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 37 publications
6
77
2
Order By: Relevance
“…S1). Our results are consistent with those observed by others: If rapamycin induces autophagy in neurons, it does so weakly (8,17). Indeed, it was suggested that rapamycin inhibits polyglutamine protein aggregation independent of autophagy (19).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…S1). Our results are consistent with those observed by others: If rapamycin induces autophagy in neurons, it does so weakly (8,17). Indeed, it was suggested that rapamycin inhibits polyglutamine protein aggregation independent of autophagy (19).…”
Section: Resultssupporting
confidence: 94%
“…Indeed, inhibition of mTOR with rapamycin and its analogue, everolimus, strongly induced autophagy in a nonneuronal cell line but very weakly, if at all, in neurons. A similar result was observed in a mouse model of HD (8). Because autophagy induction and the resulting turnover of misfolded toxic proteins have been proposed as a neuroprotective strategy for many neurodegenerative diseases, our quest for strong autophagy inducers in neurons has therapeutical implications.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As two independent laboratories, we have both shown increases in autophagic flux in primary neurons treated with rapamycin using a range of assays for autophagosome formation (2) as well as assays for autophagosome maturation (2, 3). The second line of evidence presented by Tsvetkov et al (1) asserted that a previous paper found that rapamycin did not induce autophagy in the mouse brain (4). This study, which showed modest protective effects of a rapamycin analog in a mouse model of Huntington's disease, analyzed brain LC3-II levels without lysosomal inhibitors and found nonsignificant increases.…”
mentioning
confidence: 80%
“…However, the effects of rapamycin on autophagy are less prominent than those on peripheral tissues and non-neuronal cells. Everolimus, a rapamycin analogue, stimulates autophagy in muscle but not in brain and does not reduce mutant huntingtin levels in the R6/2 mouse model of HD [11]. Another paper reported that mTOR-dependent but everolimus-independent mechanisms regulate autophagy and huntingtin-aggregate degradation in cells of neuronal origin [12].…”
Section: Rapamycin In Neurodegenerative Diseasesmentioning
confidence: 99%